Darier’s Disease with Comedons - Khan, Ikram-ullah; Khalil, Uzma (International Journal of Pathology, 2018)
Darier’s disease is an uncommon genodermatosis which is difficult to recognize & usually refractory to treatment. Wepresent a variant of Darier’s disease with comedons showing histological features of Darier’s disease